Whistleblowing Financial Fraud: Integration Model of Hexagon Fraud and Theory of Planned Behavior - Dabella Yunia; Siti Mutmainah (AFRE (Accounting and Financial Review), 2024)
This research aimed to test the determinants of whistleblowing intention using an integrated method to hexagon fraud elements and the theory of planned behavior (TPB). The elements of hexagon fraud in the form of ego, capability, and opportunity were perceived behavior control, while hexagon fraud in the form of incentives and collusion were subjective norm. An attitude toward whistleblowing was part of rationalization since certain actions are justified by an individual. Data collection was conducted through a survey of 219 respondents and processed using the Partial Least Square (PLS) version 3 statistical tool and quantitative method. The result showed that ego, capability, and opportunity integrated into perceived behavior control positively affected whistleblowing intention. In addition, incentives and collusion integrated into subjective norm as well as attitude toward behavior positively affected the variable. Hexagon fraud integration model and TPB were suitable for use in whistleblowing intention. From a practical perspective, this research contributed to organizations implementing whistleblowing by considering perceived behavior control, subjective norm, and attitude.DOI: https://doi.org/10.26905/afr.v7i2.12878Â